Pengaruh Kepemimpinan Kolaboratif dan Perilaku Kreatif Terhadap Kinerja Karyawan dengan Motivasi Intrinsik sebagai Variabel Intervening (Studi Pada BPJS Ketenagakerjaan Di Madura) - Muhammad, Suma Aji Nur; Anshori, Mochammad Isa (Jurnal Kajian Ilmu Manajemen (JKIM), 2024)
This research aims to examine the influence of collaborative leadership on employee performance, the influence of creative behavior on employees, the influence of intrinsic motivation on employee performance, the influence of collaborative leadership on intrinsic motivation , the influence of creative behavior on intrinsic motivation, the influence of collaborative leadership on employee performance through intrinsic motivation, and the influence of creative behavior on employee performance through intrinsic motivation. This research uses a quantitative approach with the method of distribution of questionnaires distributed to employees of BPJS Employment in Madura. The results of the data analysis show (H1) that collaborative leadership positively but not significantly influences employee performance. (H2) collaborative leadership positively and significantly influences employee performance. (H3) collaborative leadership positively and significantly influences employee performance. (H3) intrinsic motivation positively but not significantly influences employee performance. (H4) creative behavior positively but not significantly influences employee performance. (H5) creative behavior influences employee performance in a positive and significant way. (H6) collaborative leadership positively influences employee performance, mediated by intrinsic motivation. (H7) creative behavior positively influences employee performance, mediated by intrinsic motivation.